Marschner's mineral nutrition of higher plants - Marschner, Horst; Marschner, Petra (London ; Waltham, MA : Elsevier/Academic Press, 2012)
"Respected and known worldwide in the field for his research in plant nutrition, Dr. Horst Marschner authored two editions of Mineral Nutrition of Higher Plants. His research greatly advanced the understanding of plant nutrition ranging from rhizosphere processes to nutrient uptake and utilization by plants in the field. While visiting field experiments in West Africa in 1996, Dr. Marschner contracted malaria and passed away, and until now this legacy title went unrevised. Despite the passage of time, it remains the definitive reference on plant mineral nutrition. Since the last edition, great progress has been made in the understanding of various aspects of plant nutrition. In recent years, the perspective on the mode of action of nutrients in plant metabolism and yield formation has shifted. Much progress has been made in the molecular aspects of nutrient uptake and transport within plants as well as the responses of plants to nutrient deficiency or toxicity. These and many other developments are covered in this long-awaited new edition."--P. [4] of cover.
Part I. Nutritional Physiology -- 1. Introduction, definition and classification of nutrients -- 2. Ion uptake mechanisms of individual cells and roots: short-distance transport -- 3. Long distance transport in the xylem and phloem -- 4. Uptake and release by leaves and other aerial plant parts -- 5. Mineral nutrition, yield and source-sink relationships -- 6. Functions of macronutrients -- 7. Function of nutrients : micronutrients -- 8. Beneficial elements -- 9. Nutrition and quality -- 10. Relationship between nutrition, plant diseases and pests -- 11. Diagnosis of deficiency and toxicity of nutrients -- Part II. Plant-Soil Relationships. 12. Nutrient availability in soils -- 13. Effect of internal and external factors on root growth and development -- 14. Rhizosphere Chemistry in relation to plant nutrition -- 15. Rhizosphere Biology -- 16. Nitrogen Fixation -- 17. Adaptation of plants to adverse chemical soil conditions -- 18. Nutrient and carbon fluxes in terrestrial agro-ecosystems.
Previous ed. 1995.
Includes bibliographical references (p. 483-643) and index.
Keywords: Plants -- Nutrition; Plants -- Effect of minerals on; Plant-soil relationships; Crops -- Nutrition; Crops and soils; Soil mineralogy